Hate speech as limitation to freedom of expression - Sedols, Roberts Kārlis (Riga Graduate School of Law, 2018)
The aim of the thesis is to provide a reasonable solution for the absence of a definition of hate speech, which could be applied within the case law of European Court of Human Rights concerning freedom of expression. The problem arises as a result of the ambiguity of “hate speech” as it has no universal definition, therefore creating a legal problem – when the right to freedom of expression is exercised and leads to legal consequences where the interpretation of freedom of expression is uncertain, in some cases it is unclear whether the expression constitutes as a hate speech or not.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Freedom of expression; Hate speech